2020
DOI: 10.5194/acp-20-10091-2020
|View full text |Cite
|
Sign up to set email alerts
|

Airborne measurements and large-eddy simulations of small-scale gravity waves at the tropopause inversion layer over Scandinavia

Abstract: Abstract. Coordinated airborne measurements were performed by two research aircraft – Deutsches Zentrum für Luft- und Raumfahrt (DLR) Falcon and High Altitude and Long Range Aircraft (HALO) – in Scandinavia during the GW-LCYCLE II (Investigation of the life cycle of gravity waves) campaign in 2016 to investigate gravity wave processes in the upper troposphere and lower stratosphere (UTLS) region. A mountain wave event was probed over southern Scandinavia on 28 January 2016. The collected dataset constitutes a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Doppler wind LiDARs (DWLs) are the international standard for wind measurements and have been used for among other things 1) data assimilation experiments (Horányi et al, 2015;Pu et al, 2017;George et al, 2021, e.g.,), 2) to study for instance turbulence, gravity waves, orographic effects (Yuan et al, 2020;Gisinger et al, 2020;Baidar et al, 2020, e.g.,), and 3) to monitor the flow in wind farms (Käsler et al, 2010;Wagner et al, 2017;Zhan et al, 2020;Schneemann et al, 2021, e.g.,). The coherent detection DWL employed in this study has a wavelength of 2022.54 nm (approximately 2 µm), being eye-safe and operating in the Rayleigh scattering regime.…”
Section: Airborne Doppler Wind Lidarmentioning
confidence: 99%
“…Doppler wind LiDARs (DWLs) are the international standard for wind measurements and have been used for among other things 1) data assimilation experiments (Horányi et al, 2015;Pu et al, 2017;George et al, 2021, e.g.,), 2) to study for instance turbulence, gravity waves, orographic effects (Yuan et al, 2020;Gisinger et al, 2020;Baidar et al, 2020, e.g.,), and 3) to monitor the flow in wind farms (Käsler et al, 2010;Wagner et al, 2017;Zhan et al, 2020;Schneemann et al, 2021, e.g.,). The coherent detection DWL employed in this study has a wavelength of 2022.54 nm (approximately 2 µm), being eye-safe and operating in the Rayleigh scattering regime.…”
Section: Airborne Doppler Wind Lidarmentioning
confidence: 99%
“…Further, it has been shown that mountain waves can be advected over large distances, and in the stratosphere do not necessarily occur over the mountain range where they were excited (e.g., Krisch et al, 2017). Still, mountain waves are often observed near their sources, for example over Scandinavia (e.g., Doernbrack and Leutbecher, 2001;Gisinger et al, 2020). Therefore, to include also a region in the Northern Hemisphere wave sources (Southern Ocean and northern hemisphere polar night jet regions) and PDFs that are more strongly dominated by orographic sources (South America region).…”
Section: Gravity Wave Momentum Flux Pdfs In the Respective Winter Hem...mentioning
confidence: 99%
“…4). To study the interaction of the GWs with the tropopause by in situ observations (Gisinger et al, 2020), two flight legs were positioned below (legs 1 and 2) and two flight legs above the tropopause (legs 3 and 4). Both lower legs were performed at 61 • N (leg 1 from point A to point B and leg 2 from point B to point A) and were mainly dedicated to in situ and water vapour observations by BAHAMAS and WALES.…”
Section: Gloria Measurements and Diagnosticsmentioning
confidence: 99%
“…So far several measurement techniques have been developed to fully characterise gravity waves. For example, in situ measurements of close-to-vertical profiles taken by radiosondes, dropsondes, or falling spheres can be analysed using hodograph analysis, the Stokes method, or a combination of wind and temperature measurements to fully characterise gravity waves (Eckermann and Vincent, 1989;Guest et al, 2000;Wang and Geller, 2003;Zhang et al, 2014), though sampling errors of nearly vertical profiles may introduce biases (e.g. Vosper and Ross, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation